2016
DOI: 10.1093/jjco/hyw001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety comparison of laparoscopy-assisted versus open gastrectomy for advanced gastric carcinoma with D2 lymphadenectomy

Abstract: Objective: Laparoscopy-assisted gastrectomy for advanced gastric cancer still remains controversial. The aim of this study is to compare oncologic feasibility and technical safety of laparoscopic versus open gastrectomy for advanced gastric cancer with D2 lymphadenectomy by comparing patients' short-term postoperative outcomes. Methods: One hundred and one patients with laparoscopy-assisted gastrectomy and 101 patients with open gastrectomy were one-to-one matched and then compared in terms of operative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…In the present survey, although the background of surgical procedures as well as the classification of benign or malignant disease differed between endoscopic and open surgery, PI were less frequent after endoscopic surgery, especially for esophageal surgery, gastrointestinal surgery, colorectal surgery, and cholecystectomy. Previous studies reported similar results regarding endoscopic surgery versus open surgery in esophageal surgery (23.5% vs 46.7%), gastrointestinal surgery (1.0% vs 1.8%‐8.9%), colorectal surgery (7.0%‐11.3% vs 15.7%‐25.0%), and cholecystectomy (0.6%‐5.9% vs 4.9%‐19.9%) . In the present survey, there was no incidence of PI after endoscopic esophageal surgery, although the procedures included only esophageal surgery for benign disease, such as esophageal achalasia, hiatus hernia, and selective vagotomy.…”
Section: Discussionsupporting
confidence: 73%
“…In the present survey, although the background of surgical procedures as well as the classification of benign or malignant disease differed between endoscopic and open surgery, PI were less frequent after endoscopic surgery, especially for esophageal surgery, gastrointestinal surgery, colorectal surgery, and cholecystectomy. Previous studies reported similar results regarding endoscopic surgery versus open surgery in esophageal surgery (23.5% vs 46.7%), gastrointestinal surgery (1.0% vs 1.8%‐8.9%), colorectal surgery (7.0%‐11.3% vs 15.7%‐25.0%), and cholecystectomy (0.6%‐5.9% vs 4.9%‐19.9%) . In the present survey, there was no incidence of PI after endoscopic esophageal surgery, although the procedures included only esophageal surgery for benign disease, such as esophageal achalasia, hiatus hernia, and selective vagotomy.…”
Section: Discussionsupporting
confidence: 73%
“…Short-term outcomes (for example, blood loss, time to first flatus, length of hospital stay, and postoperative complications) favour laparoscopic compared with open gastrectomy [27][28][29][30][31][32][33][34] . Those observations are based on one systematic review and several more recent primary studies.…”
Section: Key Evidence For Recommendationmentioning
confidence: 99%
“…There was no significant difference in survival and time to recurrence between the 2 surgical techniques for upper and diffuse tumours, however there was significantly better survival and time to recurrence when laparoscopic surgery was performed for mid and lower tumours ( Fig. 4 (6) showed more rapid postoperative recovery in the laparoscopic gastrectomy group compared to the open gastrectomy group, with significantly earlier first flatus time, diet start time, and significantly shorter hospital stay. The 30-day morbidity and mortality rates in this study are consistent with the rates reported in other centres.…”
Section: Fig1 Kaplan Meier Curve For Survival (1a) and Time To Recurmentioning
confidence: 93%